Implementasi Kebijakan Pengurangan Penggunaan Kantong Plastik (Studi Pada Pasar Wonokromo Kota Surabaya) - Salsabilla, Natasya; Rosdiana, Weni (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The Policy on Reducing the Use of Plastic Bags is one of the policies made by the Mayor of Surabaya which is guided by the Mayor of Surabaya Regulation Number 16 of 2022 concerning Reducing the Use of Plastic Bags which aims to reduce waste generation from plastic bags that are difficult to decompose and build community participation in environmental management and protection. . The purpose of this research is to describe and analyze the implementation of policies to reduce the use of plastic bags (study at Wonokromo Market). The type of research used is descriptive qualitative research using the theory of Donald Van Meter and Carl Van Horn covering resources, policy standards and targets, characteristics of implementing agents, inter-organizational communication and implementing activities, attitudes or tendencies of executors (dispositions), social environment, economy and politics. The data collection techniques used were observation, interviews and documentation while the data analysis techniques in this study used qualitative analysis techniques according to Miles and Huberman including data reduction, data presentation, drawing conclusions. The results of this study indicate that the Implementation of the Policy on Reducing the Use of Plastic Bags (Study at the Wonokromo Market) is running less than optimally, this is based on the implementation variable of Donald Van Meter and Carl Van Horn, namely human resources, there is already an implementation team for the policy, but in terms of quality and quantity inadequate, financial resources are only available for funds to pay the implementing team no funds for infrastructure, other activities or funds to replace plastic bags, time resources are also not optimal because the implementing team is not intense enough to socialize.   Keywords: Policy Implementation, Plastic Waste, Wonokromo Market